2019
DOI: 10.4103/ijabmr.ijabmr_404_18
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the orbital aperture in North Indian Population: A retrospective digital forensic study

Abstract: Introduction: The morphometric variations seen in the orbital aperture play a significant role in forensic anthropology, for determining the personal and gender identification, especially in case of mass disasters. Aim: The aim of the present study was to evaluate the orbital aperture dimensions along with interorbital distance as observed on posteroanterior (PA) cephalograms for personal and gender identification. Materials and Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Finally, biorbital and interorbital width were both significantly higher in Roma than in Serbian examinees. Interorbital width is earlier described as one of the sexually dimorphic morphological parameters of the skull [21], but we did not find statistically significant difference, although it was greater in males. In accordance with similar studies [17], biorbital width was found as sexually dimorphic in Serbian examinees, with higher values among males, while in Roma this sex difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Finally, biorbital and interorbital width were both significantly higher in Roma than in Serbian examinees. Interorbital width is earlier described as one of the sexually dimorphic morphological parameters of the skull [21], but we did not find statistically significant difference, although it was greater in males. In accordance with similar studies [17], biorbital width was found as sexually dimorphic in Serbian examinees, with higher values among males, while in Roma this sex difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 88%
“…Standard anatomical points were determined and used for the measurement of the orbital width, height, biorbitalinterorbital diameter and the orbital index. Orbital width -laterally curved distance between the dacryon (the point where frontal, lacrimal and maxillary bones intersect and the medial margin of the orbit is formed) and ectoconchion (the point of intersection of the anterior surface of the lateral limit of the orbit; the line divides the orbit along its axis into two parts) (Figure 1) [8]; orbital height -distance between the superior and inferior orbital margins; it is perpendicular to its width and similarly divides the orbit into two parts (Figure 1) [8]; orbital index -orbital height/orbital width × 100 [21]; biorbital width -distance between left and right ectoconchion (Figure 1) [8]; interorbital width -distance between right and left dacryon (Figure 1) [8]. Measurements were performed on coronal plane using 3D images reconstructed from orbital images.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary knowledge of these measurements is essential for correct application since they vary from one population to another. The literature shows that there are significant differences in orbital and nasal morphometry between individuals in relation to age, sex, and ethnicity [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This supracutaneous mechanism, might provide a substantial periocular area in which viral particles could land and be "funnelled" onto the ocular surface and beyond. Table 1 provides available information on the size of the orbital opening [32] and reviewed in [33], which likely underestimates the area of eyelid skin. We have estimated eyelid skin to be~4000 mm 2 and that of the brow to be~3000 mm 2 , so that in total with the ocular surface area, a landing site of~10,000 mm 2 would be available, -2 orders of magnitude greater than for the nares and mouth.…”
Section: Is the Ocular Surface An Entry Point For Sar-cov2?mentioning
confidence: 99%